Microvessel density as a prognostic factor in penile squamous cell carcinoma - Al-Najar, Amr A.; Bolenz, Christian (Urologic oncology, 2012)
Objective To examine the potential effect of tumor-induced angiogenesis in squamous cell carcinoma of the penis as a possible prognostic factor. Patients and methods Immunohistochemistry was preformed to detect microvessels in tumor samples of 64 patients with squamous cell carcinoma of the penis. We used a monoclonal mouse antibody directed against CD34 antigen. Only 61 (30 with and 31 without metastasis) patients had good staining properties and were included. After immunostaining, the entire tumor section was scanned microscopically at low power (×40) to identify hot spots within the tumor and at its periphery. Individual tumor microvessels were then counted under high power (×200) to obtain a vessel count in a defined area, and the mean of the 3 highest microvessel counts was taken as the microvessel density (MVD). Microvessel counting was performed using a computer-aided image analysis system. The nodal status was based on histopathologic examination or an uneventful follow-up ≥2 years. Results The 5-year overall survival (OAS) was 75% and 30 % for those with high and low peritumoral MVD, respectively (log rank P = 0.01). No difference was noticed within the tumor with regard to high (5-year OAS of 65.03%) and low (5-year OAS of 60.56%) intratumoral MVD (log rank P = 0.99). The mean intratumoral MVD was 32.35 (3.16), 37.94 (3.35), and 62.66 (5.47) in T1, T2, and T3 respectively (ANOVA P = 0.0006), with increasing tendency. The mean peritumoral MVD was 55.91 (5.60), 56.8 (4.00), and 78.86 (8.71), respectively (P = 0.06). No correlation between MVD lymph node status and tumor grade was seen (P > 0.05). Conclusion In our group of patients, a high peritumoral MVD was associated with a better 5-year OAS. However, for a reliable and reproducible assessment of tumor angiogenesis in penile squamous cell carcinoma, validation procedures and quality control protocols are mandatory.